AB1199 BARRIERS AND FACILITATORS TO THE IMPLEMENTATION OF A STRATIFIED MODEL OF CARE FOR LOW BACK PAIN PATIENTS IN PRIMARY CARE IN PORTUGAL. (June 2019) - Caeiro, Carmen; Paiva, Sofia; Gomes, Luis; Fernandes, Rita; Canhão, Helena; Rodrigues, Ana Maria; Sousa, Rute; Fryxell, Ana Cristina; Vicente, Lilia; Branco, Jaime; Cruz, Eduardo B.
Abstract : Background: The results of a recent study have suggested that the current clinical practice is not in line with clinical guideline recommendations and may not be delivering the best outcomes to Low Back Pain (LBP) Portuguese patients. Since the stratified primary care approach has demonstrated clinical and cost-effectiveness in the UK and other countries, the SPLIT project aimed to introduce a similar approach that involves general practitioners (GPs) and physiotherapists (PTs) in the triage and targeted treatment for LBP patients, in Portugal. In order to facilitate the implementation of this project a training program for GPs and PTs was delivered by rheumatologists and PTs. Considering the specific organization of the Portuguese primary care, it was important to explore the perceptions of the GPs and PTs, who attended to the training, regarding the implementation of the SPLIT stratified model of care in the Portuguese context. Objectives: Identify and understand the potential barriers and facilitators to the implementation of the SPLIT stratified model of care. Methods: After obtaining ethical approval, two focus groups (one for each professional group) were carried out. The focus groups were based on a semi-structured interview schedule, audio-recorded and transcribed verbatim. A thematic analysis was conducted. Firstly, two researchers independently coded the transcripts. Secondly, these researchers discussed the codes and examined their scope and relevance. Thirdly, the researchers developed a coding scheme that included the main themes and sub-themes, as well as the connections among them. Results: The potential barriers were identified and explored by both professional groups. The introduction of change into the routine delivery care was identified as one of the most important barriers. According to the GPs` perspective, the possibility of inadequate referral was considered as an issue. The PTs highlighted the challenges inherent to the psychosocial informed physiotherapy treatment of patients classified with high risk of developing persistent and disabling pain. More specifically, they emphasised the need to receive mentoring sessions in clinical practice, in order to develop competences for the management of psychosocial issues. In what concerns to the potential facilitators to the implementation of the model, the participants` personal motivation was considered as one of the most important factors. The alignment of the SPLIT model with the mission and goals of the health care units where the project was going to be piloted was also identified as an important facilitator. Finally, both professionals groups considered that the SPLIT model may facilitate the interdisciplinary approach to the management of this condition, as it clarifies the specific contribution of GPs and PTs in the approach to LBP patients Conclusion: The knowledge about the potential barriers and facilitators to the implementation of the SPLIT stratified model of care may contribute to the successful implementation of stratified care for LBP patients in Portugal. References: [1] Foster, N., et al. (2018) Prevention and treatment of low back pain: evidence, challenges, and promising directions. Lancet. 10137(391): 2368-2383. [2] Gouveia, N., et al. (2016) Prevalence and social burden of active chronic low back pain in the adult Portuguese population: results from a national survey. Rheumatology International. 36(2): 183-97. Disclosure of Interests: None declared